2023
DOI: 10.3390/brainsci13030460
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Alterations as Potential Biomarkers of Structural Brain Changes in Alzheimer’s Disease Spectrum Patients

Abstract: Retinal imaging being a potential biomarker for Alzheimer’s disease is gradually attracting the attention of researchers. However, the association between retinal parameters and AD neuroimaging biomarkers, particularly structural changes, is still unclear. In this cross-sectional study, we recruited 25 cognitively impaired (CI) and 21 cognitively normal (CN) individuals. All subjects underwent retinal layer thickness and microvascular measurements with optical coherence tomography angiography (OCTA). Gray matt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 73 publications
1
0
0
Order By: Relevance
“…Although multiple works have demonstrated a significant association between retinal structural changes (retinal nerve fiber layer (RNFL) and macular thinning mostly) and brain atrophy [ 59 – 64 ], few publications have focused on the specific relationship of retinal vasculature with brain structural changes. Similar to our results, Hu et al showed a positive association between retinal VD and gray matter volumes of the hippocampal subfields in 25 cognitively impaired patients (17 MCI and 8 AD dementia) [ 65 ].…”
Section: Discussionsupporting
confidence: 91%
“…Although multiple works have demonstrated a significant association between retinal structural changes (retinal nerve fiber layer (RNFL) and macular thinning mostly) and brain atrophy [ 59 – 64 ], few publications have focused on the specific relationship of retinal vasculature with brain structural changes. Similar to our results, Hu et al showed a positive association between retinal VD and gray matter volumes of the hippocampal subfields in 25 cognitively impaired patients (17 MCI and 8 AD dementia) [ 65 ].…”
Section: Discussionsupporting
confidence: 91%
“…FAZ area was lager in comparison to HC [10,29,37]. Researchers have also found that correlations between SRCP and disease duration [23], degree of cognitive impairment [23,36,42,49], and brain parenchymal volume [50] in AD patients continue to manifest. Biscetti et al found that the retinal FD is correlated with the CSF Aβ42/t-tau ratio [43].…”
Section: Ad and Ad-induced Cognitive Impairmentmentioning
confidence: 98%
“…Previous studies using OCT to observe retinal and choroidal thickness in patients with chronic migraine have found that migraine with or without aura cause varying degrees of impairment to the retinal structure and vascular system. The RNFL [50][51][52][53] and choroidal thickness [51,54] are significantly thinner in migraine patients compared to HC. A study using OCTA in migraine patients also found that choroidal thickness in migraine patients correlated with the disease duration.…”
Section: Migrainementioning
confidence: 99%
“…It must be noted that many of the imaging biomarkers discussed above are not specific to various forms of cardiovascular disease. For instance, many forms of dementia, such as Alzheimer's and Parkinson's Disease, have been associated with reduced vessel density in various layers of the retina when examined with OCTA [114][115][116]. Furthermore, parameters such as reduced vessel density in the various vascular layers of the retina are associated with multiple disease states of interest, such as chronic CVD (including hypertension and diabetes) and also acute stroke or MI risk.…”
Section: Limitationsmentioning
confidence: 99%